2006
DOI: 10.1080/17402520600554930
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against β2‐Glycoprotein I Complexed With an Oxidised Lipoprotein Relate to Intima Thickening of Carotid Arteries in Primary Antiphospholipid Syndrome

Abstract: To explore whether antibodies against b 2 -glycoprotein I (b 2 GPI) complexed to 7-ketocholesteryl-9-carboxynonanoate (oxLig-1) and to oxidised low-density lipoproteins (oxLDL) relate to paraoxonase activity (PONa) and/or intima media thickness (IMT) of carotid arteries in primary antiphospholipid syndrome (PAPS). As many as 29 thrombotic patients with PAPS, 10 subjects with idiopathic antiphospholipid antibodies (aPL) without thrombosis, 17 thrombotic patients with inherited thrombophilia and 23 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…PONa inversely correlated to the carotid IMT. IgG anti-β2-GPI/oxLig1 may be involved in PAPS-related atherogenesis via decreased PON activity [37].…”
Section: Atherosclerosis and Antiphospholipid Syndrome Clinical Evidmentioning
confidence: 99%
“…PONa inversely correlated to the carotid IMT. IgG anti-β2-GPI/oxLig1 may be involved in PAPS-related atherogenesis via decreased PON activity [37].…”
Section: Atherosclerosis and Antiphospholipid Syndrome Clinical Evidmentioning
confidence: 99%
“…Ames et al . described a direct association of IgG anti‐oxLDL–β2‐GP1 complexes with IMT in primary antiphospholipid syndrome (PAPS), suggesting a potential atherogenic role of these antibodies 42 …”
Section: Anti‐oxldl‐β2‐gp1 Complex Antibodiesmentioning
confidence: 99%
“…6 Ames et al described a direct association of IgG anti-oxLDL-β2-GP1 complexes with IMT in primary antiphospholipid syndrome (PAPS), suggesting a potential atherogenic role of these antibodies. 42 Another aspect is that oxLDL-β2-GP1 complex binds C-reactive protein (CRP). 43 CRP is an acute-phase plasma protein principally expressed and induced in the liver under the regulation of the proinflammatory cytokines IL-1, IL-6, and TNF-α, although nonacute-phase elevations may occur in several chronic inflammatory diseases, such as RA and atherosclerosis.…”
Section: Anti-oxldl-β2-gp1 Complex Antibodiesmentioning
confidence: 99%
“…oxLDL can bind to β2-GPI and form β2-GPI/oxLDL complexes [ 21 23 ], prompting macrophages to phagocytize oxLDL through the β2-GPI autoantibody-mediated pathway, thus inducing the formation of foam cells that participate in atherosclerosis and vascular diseases. It has been shown that the plasma levels of β2-GPI/oxLDL complexes are significantly increased in patients with microvascular diseases such as chronic inflammatory response and some autoimmune diseases [ 24 27 ], as well as with macrovascular diseases [ 28 30 ] and T2DM [ 24 , 31 ]. Nevertheless, the exact contribution of β2-GPI/oxLDL to the occurrence of cerebral infarction in T2DM is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%